The hitchhiker's guide to the galaxy - Adams, Douglas, 1952- (New York : Harmony Books, 1989)
Seconds before Earth is demolished to make room for a galactic freeway, an earthman is saved by his friend. Together they journey through the galaxy.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Dent, Arthur (Fictitious character) -- Fiction; Prefect, Ford (Fictitious character) -- Fiction; Voyages, Imaginary; Dent, Arthur (Fictional character) -- Fiction; Imaginary voyages; Prefect, Ford (Fictional character) -- Fiction; Science fiction